Expressing REQUEST in German and Russian: A Communicative-pragmatic Field Analysis; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Kotorova E. G. Elizaveta Georgievna (2015, 2015)
Title screen